“EXPRESS JUDGES” IN THE LIGHT OF THE PRINCIPLES OF EFFECTIVENESS, CELERITY AND REASONABLE DURATION OF THE PROCESS - da Fonseca, Juscelino Pires; Gomes Júnior, Luiz Manoel; Cardoso, Kelly (Revista Inclusiones, 2021)
The research starts from the incessant search of the operators of the law for faster decisions, therefore, following the principle of reasonable duration of the process in an effective way, since a quick decision will not always mean the provision of jurisdiction in an effective and appropriate way. The problem refers to the realization of these principles without the suppression of fundamental rights of the parties involved in the process, since a quick decision, if not appropriate, may have the opposite effect rendering the provision of tutelage innocuous or incurring a delay in readjusting it. her legality. Thus, the objective is to analyze these principles, investigating the risks of a quick decision and the need for effective realization of rights. To do so, it uses the deductive methodology, analyzing the current legislation and related doctrines, demonstrating the need for conjunction between the assistance of the parties, the judge, as well as, the proper interpretation of the rule in search of judicial balance.